Assessing visitors’ behavioural intention, preferences and willingness to pay on Malayan tiger conservation in Taman Negara, Pahang, Malaysia - Mzek, Tareq (2021)
The population of the unique and critically endangered species Malayan tiger (Panthera tigris jacksoni) continues to decline to less than 200 in the wild, demanding immediate attention to apply conservation action plans. Thus, this study aimed to determine visitors‟ behaviour, preferences and the estimation of their willingness to pay for Malayan tiger conservation attributes in Taman Negara, Pahang, which is one of the Malaysian national parks. The motivation of this study is to highlight the factors that impact the intention to pay for tiger conservation and estimates the visitors' estimated willingness to pay for tiger conservation attributes. Structural Equation Modelling was utilised to determine the impact of attitude, subjective norms and perceived behavioural control on visitors‟ willingness to pay toward Malayan tiger conservation. While, Choice Experiment method was used to identify visitors preferences and willingness to pay for Malayan tiger conservation attributes by estimating multinomial, mixed logit and latent class models. The selected attributes were the number of tigers in the next 12 years, the number of tiger prey, rangers, frequency of awareness programmes near tiger habitats, size of buffer zones, and conservation fee. The estimations were done with basic and interaction models of visitors‟ socio-demographic characteristic in multinomial and mixed logit models. The data was collected from 315 visitors‟ of Taman Negara, Pahang, ranging from 18 years old and above, with different sociodemographic characteristics. Results showed that attitude, subjective norms and perceived behavioural control have a significant positive impact on visitors‟ intention to pay for Malayan tiger. Furthermore, Choice Experiment results revealed that all attributes were significant and exhibited the sign as expected, except for the high number of tiger prey. This attribute was insignificant in the MXL interaction model. Increasing the number of tigers in the next 12 years was the most preferred attribute with the willingness to pay varying from MYR15.42 to MYR18.07 between the models. The results also revealed that education and gender significantly impacted visitors‟ preferences. Visitors with high education level are willing to pay to increase tigers‟ prey. In addition, males are willing to pay to increase the awareness programme frequency, whereas females are willing to pay to increase the number of prey and rangers. In the LCM model identified the existence of heterogeneity in 2 classes. The most preferred attribute in class 1 was increasing the number of tigers (Tign3). Meanwhile in class 2, the most preferred attribute was increasing the number of rangers (Rang3). Moreover, this study provided information related to visitors‟ knowledge and awareness toward Malayan tiger current situation and the importance of Malayan tiger. The results showed a significant positive impact of attitude, subjective norms and perceived behavioural control on the intention to pay for the Malayan tiger conservation. Additionally, the results were robust across estimation models and showed that the visitors are willing to pay to conserve the Malayan tigers, and increasing the tigers‟ population was a priority. These findings would support policymakers in applying an efficient conservation budget allocation to develop conservation management plans.